HOW KNOWLEDGEABLE ARE APPLIED LINGUISTICS AND SLA RESEARCHERS ABOUT BASIC STATISTICS?: DATA FROM NORTH AMERICA AND EUROPE. Issue 4 (11th September 2020) - Loewen, Shawn; Gönülal, Talip; Isbell, Daniel R.; Ballard, Laura; Crowther, Dustin; Lim, Jungmin; Maloney, Jeffrey; Tigchelaar, Magda
Abstract: Despite the prevalence of quantitative approaches in applied linguistics (AL) and second language acquisition (SLA) research (Gass, 2009), evidence indicates a need for improvement in analyzing and reporting SLA data (e.g., Larson-Hall & Plonsky, 2015). However, to improve quantitative research, researchers must possess the statistical knowledge necessary to conduct quality research. This study assesses AL and SLA researchers' knowledge of key statistical concepts on a statistical knowledge test. One hundred and ninety-eight AL and SLA researchers from North America and Europe responded to 26 discipline-specific questions designed to measure participants' ability to (a) understand basic statistical concepts and procedures, (b) interpret statistical analyses, and (c) critically evaluate statistical information. Results indicate that participants generally understood basic descriptive statistics, but performance on items requiring more advanced statistical knowledge was lower. Quantitative research orientation, number of statistics courses taken, and frequent use of statistics textbooks had positive influences on researchers' statistical knowledge.